Kematangan Karir Siswa SMA - H.R. Partino (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This research was aimed to verify a model of career maturity on High School students. The model suggests that career maturity is affected by many factors, i.e. counseling service, perception of study majoring, life history, self-efficacy and academic achievement. Research subjects consisted of 616 SMA students. Data was collected using career maturity inventory, psychological scale, and questionnaire methods. These instrumens had been adapted to Indonesia and their reliability and validity had been reestablished. Structural equation model was developed to analyze career maturity determinant factors. Outcomes of the analysis were used to verify the career maturity model and to find out direct, indirect and total effects. The research results showed that the theoretical model of career maturity is supported by empirical data, namely the eight category of measurement. Specifically, the research results are: 1) counselling service, perception of study majoring and life history had a significant effect on self-efficacy; 2) counselling service, perception of study majoring and life history had a significant effect on academic achievement; and 3) self-efficacy had a significant effect on academic achievement.Key words: career maturity, counseling services, perception of study majoring, life history, self-efficacy, and academic achievement.